Evaluation of the environmental impact of cubilote slags of the ¨Román Roca¨ casting - Cedeño Linares, Elisa; Cruz-Crespo, Amado; Perdomo González, Lorenzo; Simón La Rosa, Alejandro; Jerez Pereira, Rubén; Baños, Arnaldo (Centro Azúcar Journal, 2013)
At the work was established a valuation of the environmental impact of a cubilote furnace slag, hich is widely used in casting parts for sugar industry. A diagnostic of the present state of the spilling of slag to the environment was made and was valuated the potentiality of recycle it like a source of row materials. The evaluation of the environmental impact was made, from the importance matrix, the impacted factors and the impacting actions. As an example the case of the Foundry Enterprises “Enrique Villegas Martinez”, belonging to the Minister of the Sugar Industry, was showed.